Factors influencing the level of electronic commerce among central Iranian SMEs - Jamali, Negar (2012)
Small and medium-sized enterprises (SMEs) contribute heavily to economic growth,social structure and employment as well as regional and local development. Consequently, they have become a significant sector of the economy. Moving towards globalization and rapid technological changes, including the internet and e-commerce (EC), can offer new opportunities for SMEs. Researchers have recently discovered that information technology-related innovations such as EC are being used increasingly by SMEs because of their various benefits. The lack of EC research on SMEs of developing countries is challenging because the findings of previous EC studies on SMEs of developed countries cannot be freely generalized to the context of SMEs of developing countries. This lack of generalizability is due the fact that in most developing countries including Iran, and in addition to the innate limitation of SMEs, EC adoption by SMEs is also hindered by the quality, availability, and cost of accessing necessary infrastructure. Therefore, the recent literature recommends that studies should be strong enough to capture most, if not all, of the idiosyncrasies of EC adoption within SMEs of developing countries. To help SMEs, in particular those in developing countries, with EC adoption, this research investigates the factors within the Technological Organizational Environmental (TOE) framework that affect the decision to adopt EC as well as the adoption and nonadoption of different EC tools within two hundred thirty five manufacturing SMEs in central Iran. Furthermore the current research attempted to investigate the level of EC adoption in SMEs. In this research a questionnaire-based survey using a quantitative approach is conducted. The research model hypothesised ten adoption predictors within three contexts of TOE framework; relative advantage, cost, compatibility, business size, information intensity, support from technology vendors, pressure from suppliers/buyers,competition, CEO’s innovativeness, and CEO’s involvement. The findings showed that seven out of ten factors have significant positive relationships with EC adoption, which were buyer/supplier pressure, support from technology vendors, perceived compatibility,CEO innovativeness, perceived relative advantage, competition and information intensity. Moreover, results showed that 57.02 percent of SMEs adopted EC. In addition to this, there was an adoption rate of 48.50 percent for email, 29.10 percent for intranet,and 32.90 percent for extranet/VPN, 41.04 percent for web sites, 22.39 percent for EDI,13.43 percent for EFT and 11.19 percent for ESCM. However, the factors that appeared to be significant and the ones that appeared to be insignificant led to a conclusion the weakness of the EC adoption phenomenon in Iranian SMEs. This research has managerial implications for practitioners in Iran and internationally, and theoretical implications for researchers who are interested in EC adoption within SMEs.